PERMAINAN TRADISIONAL ENGKLEK SEBAGAI MEDIA PENGEMBANGAN KINESTETIK ANAK USIA DINI DI PAUD - Maya Laela Sari; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (STKIP Pesisir Selatan, 2026)
Abstract—This study aims to describe the use of the traditional engklek game as a medium for developing kinesthetic abilities in early childhood education. The study was conducted at TK YPWKS III with a school context involving 130 children and 13 teachers. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation during the implementation of engklek activities. The findings indicate that engklek provides meaningful stimulation for children’s kinesthetic development, particularly in balance, body coordination, leg muscle strength, agility, movement control, courage, and self-confidence. The game also encourages social-emotional values such as discipline, honesty, patience, turn-taking, and respect for peers. The study concludes that the traditional engklek game is a simple, low-cost, culturally meaningful, and developmentally appropriate learning medium for early childhood education